Pengembangan Pop-UP Book Digital Berbasis PowerPoint “PUNAH” Kisah Nabi Nuh A.S. Pembelajaran PAI Kelas 2 SD - Viranti, Nuzha; Azzahra, Fahira; Nurul Muna, Siti Maemunah; Aeni, Ani Nur (YASIN, 2025)
In the digital era, technological advancements pose challenges in education, particularly in providing innovative and interactive learning media. Islamic Religious Education (PAI) in elementary schools still relies heavily on conventional methods such as lectures and textbooks, which often fail to engage students effectively. As a result, students' interest and understanding of the subject matter remain suboptimal. Therefore, innovative and interactive learning media are needed to enhance student engagement in the learning process. This study aims to develop a PowerPoint-based Digital Pop-Up Book, named "PUNAH", as an interactive learning medium for second-grade elementary school students in PAI, focusing on the story of Prophet Nuh (Noah). The research employs the Design and Development (D&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through expert validation by subject matter and media specialists, as well as trials involving teachers and students. The research findings indicate that this Digital Pop-Up Book is highly suitable as a learning medium based on its clarity of content, visual appeal, ease of use, and effectiveness in enhancing students' understanding. The use of this medium has been proven to increase student engagement in learning while also assisting teachers in delivering material in a more engaging and interactive manner. In conclusion, the development of this PowerPoint-based Digital Pop-Up Book serves as an innovative solution to improve the quality of PAI learning in elementary schools, particularly in presenting the stories of the Prophets in a more engaging way for students.